If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -6 = 8x + -4x Reorder the terms: -6 + 3x = 8x + -4x Combine like terms: 8x + -4x = 4x -6 + 3x = 4x Solving -6 + 3x = 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -6 + 3x + -4x = 4x + -4x Combine like terms: 3x + -4x = -1x -6 + -1x = 4x + -4x Combine like terms: 4x + -4x = 0 -6 + -1x = 0 Add '6' to each side of the equation. -6 + 6 + -1x = 0 + 6 Combine like terms: -6 + 6 = 0 0 + -1x = 0 + 6 -1x = 0 + 6 Combine like terms: 0 + 6 = 6 -1x = 6 Divide each side by '-1'. x = -6 Simplifying x = -6
| 2(3x+4)-(3x-2)=8 | | 9-4x=5x+9 | | 6x-3=6(x+1) | | 3x+12-5*5=22 | | x/2+x/3=5/6 | | -5x+2+2x=-6x+7 | | 2k-22=8(K+1) | | (15n)+4=36 | | 17.1d=18d+17.19 | | 2n/5-6/13=74/65 | | 8x/9-5=59 | | 4(2x-7)-2=4(x-2)+6 | | .35c+9.99=11.74 | | 6.6h-7.15-16.2h=-6.6h+19.25 | | 0=-x^2+2x+6 | | 4(2x-7)-2=4(x-3)+6 | | 9.99p+.35=11.74 | | 8k-3=3-8k | | 36c^2-121g^2=0 | | x/3-2=-8 | | x^2+3x-43=0 | | y=-x^2+2x+6 | | 4x+14=6x+7 | | -5x+2+2x=6x+7 | | 38=-2(24-x)+3(x-3) | | x^3+4x^2+36x+144=0 | | 4s^2+20st+25t^2=0 | | X^2-18x+56= | | 5d+8=33 | | -2+a=15 | | 38=-2(24-x)+3(x+3) | | -0.8x=7.2 |